Transitional encounters: practices of queer futurity in K. Sello Duiker's Thirteen Cents. Issue 4 (1st October 2016) - Spain, Andrea
Abstract: This article argues that the narrative structure of K. Sello Duiker's novels highlights a disjunction between the temporality of history's promise and that of the encounter. In contrast to a temporality of the promise or a messianic nation "to come, " Duiker's novels render visible those who are deemed outside of the time of nation and history, those who are considered to be the by-products of modernity: the destitute, the sick, the jobless, the homeless, the queer. In doing so, Duiker's work dramatizes a time of encounter, or what Samuel Delany has called "contact situations, " those brief, surprising, interracial and interclass exchanges that momentarily bring about new and unscripted relationality. Focusing on the young Azure in Thirteen Cents, this article argues that for Duiker, the encounter is fragile and evanescent compared with relations defined in received networks of power, networks organized by rigid fantasies of homophobic, violent masculinities and entrenched racial and economic privilege. Even so, Duiker's work suggests that tracing itineraries of contact situations might index the potentiality of a longing in contemporary South Africa, if not for the nation as a whole, for what José Esteban Muñoz has called queer futurity: practices that suspend telos, aim and utility in order to cultivate spaces of restructured sociality outside rigid networks profit or power, even in the context of everyday gender and sexuality-based violence within South Africa's global present.